The Impact of PM2.5 on the Host Defense of Respiratory System - Yang, Liyao; Li, Cheng; Tang, Xiaoxiao (Frontiers in Cell and Developmental Biology, 2020)
The harm of fine particulate matter (PM2.5) to public health is the focus of attention around the world. The Global Burden of Disease Study (GBD) 2015 ranked PM2.5 as the fifth leading risk factor for death, which caused 4.2 million deaths and 103.1 million disability-adjusted life-years (DALYs) loss, representing 7.6% of total global deaths and 4.2% of global DALYs. Epidemiological studies have confirmed that exposure to PM2.5 increases the incidence and mortality of respiratory infections. The host defense dysfunction may be the key to the susceptibility of respiratory system infection caused by PM2.5 exposure. Thus, this review aims to assess the impact of PM2.5 on the host defense of respiratory system. Firstly, we elaborated the epidemiological evidence that exposure to PM2.5 increases the risk of respiratory infections. Secondly, we summarized the experimental evidence that PM2.5 exposure increases the susceptibility of different pathogens (including bacteria and viruses) in respiratory system. Furthermore, here we will discuss the underlying host defense mechanisms by which PM2.5 exposure increases the risk of respiratory infections as well as future perspectives.